2018
DOI: 10.4025/actasciagron.v40i1.33032
|View full text |Cite
|
Sign up to set email alerts
|

<b>Interrelationship between morphological, agronomic and molecular characteristics in the analysis of common bean genetic diversity

Abstract: ABSTRACT.The present study aimed to analyze, through 12 morpho-agronomic traits and 18 micro satellite loci, the genetic diversity in 17 common bean accessions from the Bean Germplasm Bank of the Center for Applied Agricultural Research of the State University of Maringá (BGF/Nupagri/UEM), in Paraná State, Brazil. Genetic diversity was assessed by joint analysis of phenotypic and genotypic characteristics using the Genetics platform of SAS software. To that end, a dissimilarity matrix was constructed based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…The genotypes used in this study consisted of diverse genotypes with different adaptation, which lead to deviation from their genetic potential. Inconsistencies between genotype and phenotype expressions have been reported previously in common beans (Phaseolus spp) [66]. A combined dendrogram based on genotypic and phenotypic data improves precision in genetic analyses of germplasm [67,68].…”
Section: Plos Onementioning
confidence: 90%
“…The genotypes used in this study consisted of diverse genotypes with different adaptation, which lead to deviation from their genetic potential. Inconsistencies between genotype and phenotype expressions have been reported previously in common beans (Phaseolus spp) [66]. A combined dendrogram based on genotypic and phenotypic data improves precision in genetic analyses of germplasm [67,68].…”
Section: Plos Onementioning
confidence: 90%
“…In addition, the inconsistences between genotypic and phenotypic matrices could be due to the fact that genotyping may be able to capture subtle genetic mutations across the whole genome that may not be expressed phenotypically. Other studies reported inconsistences between phenotypic and genotypic matrices in common beans (Phaseolus spp) [45]), yam (Dioscorea spp) [46] and Brassica spp. [46].…”
Section: Population Structure and Genetic Parametersmentioning
confidence: 97%
“…In addition, the inconsistences between genotypic and phenotypic matrices could be due to the fact that genotyping may be able to capture subtle genetic mutations across the whole genome that may not be expressed phenotypically. Other studies reported inconsistences between phenotypic and genotypic matrices in common beans (Phaseolus spp) [47]), yam (Dioscorea spp) [48] and Brassica spp [48]. Due to the expected discord between genotypic and phenotypic matrices, the use of a joint matrix derived from combined phenotypic and genotypic matrices has been recommended to increase precision [49; 50].…”
Section: Associations Of Quantitative Traitsmentioning
confidence: 99%